Implementasi Big Data Analytics dan Opini Audit terhadap Kualitas Audit dengan Audit Delay Sebagai Variabel Mediasi - Anisa Listya; Aspahani Aspahani; Christian Damar Sagara Sitepu (Owner : Riset dan Jurnal Akuntansi, 2023)
This research is based on the relationship between Big Data Analytics and its impact on the quality of audit evidence and the level of assurance felt by end users of financial statements. Big Data Analytics potentially play an important role in innovative auditing practices. Big Data Analytics can increase the efficiency and effectiveness of financial statement audits, but additional competencies and technological capabilities are required to implement Big Data Analytics. With Big Data, auditors can minimize the risks posed by sampling, and therefore, provide a reasonable level of assurance. This study aims to examine Big Data Analytics variables and audit opinion whether these two variables are antecedent variables of audit delay and affect audit quality. This study uses secondary data in the form of the company's annual financial report. The population in this study are all companies listed on the Indonesia Stock Exchange (IDX). The population in this study were 100 companies in the telecommunications, transportation and banking sub-sectors that met the criteria and had been determined to be related to problems during the 2016 to 2020. The data analysis technique in this study was to use the Structural Equation Model to examine the mediating effect. The implementation of big data analytics has no effect on the audit delay variable. Based on the research results, there is sufficient evidence that audit opinion has a significant positive effect on audit delay. However, there is not enough evidence that BDA has a significant positive effect on audit delay